Fragment depicting several human figures - Temples of India Project Team (Jio Institute, 2024)
The fragments, on Harsha Hill, depict several human figures in diverse actions, although it is unclear if they form a coherent narrative. The left extreme fragment is defaced, followed by a depiction of a female figure reclining on a couch and being served by numerous female attendants. This scene evokes the Krishna-story panels quite popular in various temple sites of Rajasthan from the 8th century CE, with some references probably dating even earlier. However, the absence of an infant on the couch makes it difficult to identify the female figure with certainty as Yashoda. On the right extreme, there are various armed figures depicted.